Good soil : the education of an accidental farmhand - Chu, Jeff (Convergent, 2025)
"In his late thirties, Jeff Chu left his job as a magazine writer and enrolled at Princeton Seminary's "Farminary," a 21-acre farm where students learn to work the earth while interrogating life's biggest questions. Now he unfolds what he learned about creating good soil-both literally and figuratively-drawing lessons from the chickens, goats, and zinnias and the rhythms of growth, decay, and regeneration that define life on the land. In a series of reflections, Chu introduces us to the cast of characters, human and not, who became his teachers. From the egrets that visited the pond, to the worms that turned waste into fertile soil, to the Chinese long beans that got passed over in the farm's CSA, Chu considers our relationship with the food on our plates, the belonging we seek, and the significance of his own roots, discovering what the earth is trying to tell us, if we'll stop and listen. In gorgeous, transporting prose, Good Soil helps readers connect to the land and to each other at a time when we are drawn most to the phones in our hands. For nature lovers, foodies, and anyone who has daydreamed about a more meaningful life, this book is a tribute to friendship, acceptance, spirituality, and how love can grow from the unlikeliest of places"--